Estudo dos efeitos da substituição de Feldspato por Filito em massas de porcelanato - Sanchez, Miguel Yesid Hernandez (Universidade Federal de São Carlos, 2018)
Porcelain stoneware tiles, porcelanatos, present excellent technical and aesthetic characteristics. In Europe, the bodies used in the manufacture of porcelain and porcelanatos are based on the classic triaxial ceramic, clay, quartz and feldspar, and the latter plays the role of flux. Bodies of this type have been thoroughly studied. In Brazil, for various reasons, virtually all the industries that produce glazed porcelain stoneware tiles replaced feldspar by the phyllites. Although this practice, the replacement of feldspar by phyllites, has already occurred for some decades, the implications of this substitution have not been properly studied. The general objective of this work was to identify and seek explanations for the differences in behavior during firing caused by the substitution of feldspar by phyllite in the bodies used in the manufacture of glazed porcelain stoneware tiles. For this, the raw materials alone, feldspar and phyllites, as well as bodies containing the same content of these raw materials, were evaluated comparatively. Based on the results produced by several characterization techniques, among them the gresification curves and the chemical composition of the vitreous phases after the firing, the following conclusions were reached: 1) the behavior of the raw materials, feldspar and phyllites during firing are quite different; 2) different phyllites exhibit significantly different behavior during firing; 3) the differences in behavior between the phyllites is mainly due to the variation of the sericite content (muscovite fine-grained mica); 4) the behavior of pure raw materials is transferred to the masses which contain them.; 5) although the minerals responsible for forming the liquid phase during firing are significantly different, a mixture of feldspar, albite and orthoclase, and sericite, the chemical compositions of the vitreous phases formed are similar; 6) the volume of liquid phase during sintering seems to be one of the main variable responsible for the observed differences in the behaviour during firing.

El porcelanato como revestimiento cerámico se destaca en el mercado mundial actual, ya que presenta excelentes características técnicas y estéticas. En Europa, las pastas utilizadas en la fabricación de porcelanas y porcelanatos se basan en el clásico triaxial cerámico, arcilla, cuarzo y feldespato, este último desempeña el papel de fundente. Estas tipologías de pastas porcelánicas fueron estudiadas exhaustivamente. En el Brasil, por diversos motivos, prácticamente todas las industrias productoras de porcelanatos esmaltados sustituyeron feldespato por filito. Aunque la práctica de sustituir feldespato por filito, ocurre hace varias décadas, no se tiene registro de ningún tratado que haya estudiado sistemáticamente sus implicaciones. El objetivo general del presente estudio fue identificar y buscar las explicaciones de las diferencias de comportamiento durante la quema producido por la sustitución de feldespato por filito en pastas utilizadas en la manufactura de porcelanatos esmaltados. Para tal fin, se evaluaron comparativamente las materias primas, feldespato e filitos, así como las pastas porcelânicas que contienen estos fundentes a una misma concentración. Los resultados encontrados por distintas técnicas de caracterización, entre ellas las curvas de gresificación y composición química de las fases vítreas después de la quema, se concluye que: 1) el comportamiento de las materias primas, feldespato e filitos durante la quema son bastante diferentes; 2) diferentes filitos presentan comportamientos significativamente diferentes durante la quema; 3) las diferencias de comportamiento entre filitos es principalmente debido a la variación de concentración de la sericita (mica moscovita de granulación fina); 4) el comportamiento de las materias primas puras es transferido a las pastas que las contienen; 5) aunque los minerales responsables por la formación de la fase líquida durante la quema sean significativamente diferentes, una mezcla de feldespatos, albita e ortoclasa, y sericita, las composiciones químicas de las fases vítreas formadas son muy similares; 6) la variación de volumen de la fase líquida durante la quema parece ser una de las principales variables responsables por las diferencias observadas.
Effects of substituting Feldspar by brazilian Phyllite in glazed porcelain bodies
Estudio de los efectos de la sustitución de Feldespato por Filito en pastas de porcelanato
Keywords: Porcelanato; Filito cerâmico; Sericita; Fluxo viscoso; Gresificação; Porcelain tile; Phyllite; Sericite; Viscous flow; Gresification; Porcelanato; Filito cerámico; Sericita; Flujo viscoso; Gresificación; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA